For a sociology of authorship in Portugal - Castro Seixas, Paulo (2020)
This article presents some of the results of the first study on the universe of authors in Portugal, conducted for the Portuguese Society of Authors (SPA), the only institutional representation of authors in the country. With the aim of making a sociography of these authors, the research was methodologically based on a quantitative approach in the form of a questionnaire survey, administered to SPA Cooperators and Beneficiaries. The results highlight some patterns of an “author culture” in Portugal, but raise several issues that indicate the relevance of greater autonomy of authorship as a sociological field of study.